(untitled) (Global Journal of Management and Business Research, 2020)
It is an article of problematization of the normative device in the law of tax executions that unrestrictedly forbids a concomitance of administrative and judicial tax proceedings. To the job and division of judicial (judicial) in the division of trial and judicial judicial; (II) to make "State-judge-of-its-owncause" to the State of Weighting; (III) Object of the action as an affirmation of law.